Understanding L2 Proficiency Theoretical and meta-analytic investigations - Jeon, Eun Hee; In'nami, Yo (Bilingual Processing and Acquisition, 2022)
This edited volume is a collection of theoretical and empirical overviews of second language (L2) proficiency based on four skills: reading, writing, listening, and speaking. Each skill is reviewed in terms of how it has been conceptualized, measured, and studied over the years in relation to relevant (sub-) constructs of the language skill under discussion. This is followed by meta-analyses of correlation coefficients that examine the relationship between the L2 skill in question and its component variables. Unlike most meta-analyses that have a limited range of variables under investigation, our meta-analyses are much larger in scope to better clarify such relationships. By combining theoretical and empirical approaches, the book is helpful in deepening the understanding of how subcomponents or various variables are related to a particular L2 skill. Contributions by: Jie Gao and April Ginther; Jan H. Hulstijn; Yo In'nami, Rie Koizumi, Eun Hee Jeon and Yuya Arai; Eun Hee Jeon, Yo In'nami and Rie Koizumi; Eun Hee Jeon and Junko Yamashita; Rie Koizumi, Yo In'nami and Eun Hee Jeon; Masumi Kojima, Yo In'nami and Taku Kaneta; Masumi Kojima and Taku Kaneta; Rob Schoonen; Elvis Wagner; Junko Yamashita